Quality of care management decisions by multidisciplinary cancer teams: a systematic review. - Lamb, B; Brown, K; Nagpal, K; Vincent, C; Green, J; Sevdalis, N (2011)
BACKGROUND: Factors that affect the quality of clinical decisions of multidisciplinary cancer teams (MDTs) are not well understood. We reviewed and synthesised the evidence on clinical, social and technological factors that affect the quality of MDT clinical decision-making. METHODS: Electronic databases were searched in May 2009. Eligible studies reported original data, quantitative or qualitative. Data were extracted and tabulated by two blinded reviewers, and study quality formally evaluated. RESULTS: Thirty-seven studies were included. Study quality was low to medium. Studies assessed quality of care decisions via the effect of MDTs on care management. MDTs changed cancer management by individual physicians in 2-52% of cases. Failure to reach a decision at MDT discussion was found in 27-52% of cases. Decisions could not be implemented in 1-16% of cases. Team decisions are made by physicians, using clinical information. Nursing personnel do not have an active role, and patient preferences are not discussed. Time pressure, excessive caseload, low attendance, poor teamworking and lack of leadership lead to lack of information and deterioration of decision-making. Telemedicine is increasingly used in developed countries, with no detriment to quality of MDT decisions. CONCLUSIONS: Team/social factors affect management decisions by cancer MDTs. Inclusion of time to prepare for MDTs into team-members' job plans, making team and leadership skills training available to team-members, and systematic input from nursing personnel would address some of the current shortcomings. These improvements ought to be considered at national policy level, with the ultimate aim of improving cancer care.